2015
DOI: 10.1155/2015/267625
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Abscess Potentially of Odontogenic Origin

Abstract: Odontogenic origins are rarely implicated in the formation of brain abscesses. The relative paucity of this kind of infection and the difficulty in matching the causative microorganisms of a brain abscess to an odontogenic source can explain the late management of patients. We herein describe a case of a 46-year-old man with a cerebellar abscess that was probably due to an odontogenic infection. The diagnosis supported by imaging and microscopic identification, mini craniectomy for abscess drainage followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Many oral bacteria are fastidious pathogens which are difficult to culture and have to be taken to the laboratory immediately under strict anaerobic conditions, therefore, standard bacterial culturing may not serve as pathogen identification [1]. As shown in Case I in the present report and as reported by Greenstein et al [17] and Ben Hadj Hassine et al [11], bacterial culture revealed the presence of only Staphylococcus. Mueller et al [18] attempted to correlate brain abscesses with subgingival microflora by use of conventional culturing techniques, and indicated the underestimation of oral infective sources in brain abscesses in view of the bacterial match between oral infective source and brain abscesses in their retrospective analyses.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Many oral bacteria are fastidious pathogens which are difficult to culture and have to be taken to the laboratory immediately under strict anaerobic conditions, therefore, standard bacterial culturing may not serve as pathogen identification [1]. As shown in Case I in the present report and as reported by Greenstein et al [17] and Ben Hadj Hassine et al [11], bacterial culture revealed the presence of only Staphylococcus. Mueller et al [18] attempted to correlate brain abscesses with subgingival microflora by use of conventional culturing techniques, and indicated the underestimation of oral infective sources in brain abscesses in view of the bacterial match between oral infective source and brain abscesses in their retrospective analyses.…”
Section: Discussionmentioning
confidence: 47%
“…There are very few case reports to date of brain abscess caused by a primary infection of odontogenic origin [1][2][3][4][5][6][7][8][9][10][11]. A recent systematic review investigating the pathogenesis, microbiology, interventions, and outcomes of brain abscesses of oral origin indicated four possible routes of odontogenic spread: (1) systemic bacteremia (hematogenous); (2) direct venous drainage via the facial and pterygoid vein systems to the cavernous sinus; (3) inoculation via contiguous extension or by introduction of foreign objects; and (4) lymphatic drainage [1].…”
Section: Introductionmentioning
confidence: 99%
“…Then, remission of neurological symptoms was achieved through the eradication of oral infections ( 1 ). In the same line, literature also shows a case of cerebral abscess, of odontogenic origin, in a 46 years old man ( 2 ). Usually, the access road to the central nervous system is through a pansinusitis.…”
Section: Introductionmentioning
confidence: 83%
“…The clinical symptoms and signs are nonspecific for brain abscesses, which present differently depending on the origin, size, and location of the abscess [ 5 ]; the virulence of the infecting organisms; and the underlying systemic conditions. The most common symptoms are headache, nausea, vomiting, fever, focal neurological deficits, and an alteration of mental status [ 7 ]. Our patient presented postoperatively with loss of consciousness and general convulsions following convulsions of the left upper and lower limbs.…”
Section: Discussionmentioning
confidence: 99%